(untitled) (Biuletyn Kryminologiczny, 2021)
Tematem niniejszego artykułu jest medialny obraz sprawcy zabójstwa i jego zbrodni. Celem artykułu jest wskazanie rozbieżności pomiędzy obrazem faktycznym zabójstwa, a jego medialnym odzwierciedleniem oraz charakterystyka odnalezionych różnic. Artykuł zawiera podstawowe zagadnienia dotyczące mediów oraz dane statystyczne Policji i Ministerstwa Sprawiedliwości odnoszące się do tego przestępstwa. Rozważania zostały poparte wynikami kwartalnego monitoringu mediów, który objął 292 doniesienia kryminalne. The subject of this article is the media image of the perpetrator of the murder and his crimes. The aim of the article is to indicate the discrepancy between the actual picture of the murder and its media representation as well as the characteristics of the diﬀerences found. The article contains basic issues regarding the media and statistical data of the Police and the Ministry of Justice statistics regarding this kind of crime. The considerations were supported by the results of quarterly media monitoring, which included 292 criminal reports.